2016
DOI: 10.3190/jgeosci.222
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic fabric and emplacement of dykes of lamprophyres and related rocks of the Central Bohemian Dyke Swarm (Central European Variscides)

Abstract: Numerous dykes of lamprophyres and various types of granitoid, syenitoid, dioritoid, and gabbroid porphyries of Variscan age crop out in the area of the Central Bohemian Plutonic Complex and adjacent high-to low-grade metamorphic units of the Moldanubian Zone and Teplá-Barrandian Unit. Magnetic fabric in fourteen dykes of lamprophyres and related rocks was investigated. Mostly, the magnetic foliation is roughly parallel to the dyke plane and the magnetic lineation is horizontal with the relics of originally st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…When compared to other Variscan lamprophyres (Štemprok et al, 2014), the Lamas de Olo specimen is depleted in Na 2 O and CaO, which is presumably due to the fluid-promoted feldspar alteration (Förster et al, 2007). Previous studies (Oliveira et al, 2019) have shown that the magnetic fabric of this lamprophyre is near-type III (Hrouda et al, 2016) because while the average magnetic lineation is subperpendicular to the dyke trend (40°/N138°E), the average magnetic foliation is oblique (N105°E-57°SW). Such magnetic fabrics have been typically attributed to postmagmatic processes (Raposo & Ernesto, 1995).…”
Section: Lamprophyre Petrogenesis and Source Compositionmentioning
confidence: 63%
“…When compared to other Variscan lamprophyres (Štemprok et al, 2014), the Lamas de Olo specimen is depleted in Na 2 O and CaO, which is presumably due to the fluid-promoted feldspar alteration (Förster et al, 2007). Previous studies (Oliveira et al, 2019) have shown that the magnetic fabric of this lamprophyre is near-type III (Hrouda et al, 2016) because while the average magnetic lineation is subperpendicular to the dyke trend (40°/N138°E), the average magnetic foliation is oblique (N105°E-57°SW). Such magnetic fabrics have been typically attributed to postmagmatic processes (Raposo & Ernesto, 1995).…”
Section: Lamprophyre Petrogenesis and Source Compositionmentioning
confidence: 63%
“…The younger MPC is composed of peraluminous (S-type) anatectic granitoids (c. 330-300 Ma), and it was formed by extensive migmatitization and isothermal decompression of the surrounding pelitic rocks. The third group is represented by potassic-ultrapotassic rocks (346-337 Ma) that form several isolated plutons ( Figure 1a) and dyke swarms [8,[36][37][38]. The last group of Variscan igneous rocks have mafic and ultramafic composition (gabbro, norite, troctolite, pyroxenite) and an age of around 340 Ma [39][40][41].…”
Section: Concise Geological Settingmentioning
confidence: 99%
“…The structural aspects of these processes have been investigated both from the theoretical and practical points of views (see, for example, [2,3] and references therein). These investigations used various indicators of magma flow, which are unfortunately scarce, and the anisotropy of magnetic susceptibility (AMS), which can be easily measured on almost all types of dyke rocks (e.g., [4][5][6][7][8][9][10][11][12][13][14]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies concerning the physical properties of lamprophyric rocks (sensu Le Maitre 2002) in the literature are rare (e.g., Rao 2008, Nishad et al 2013, Hrouda et al 2016, while studies applying geophysical techniques are almost non-existent (e.g., Machek et al 2014). Considering the relationship between lamprophyres and some types of ore deposits and the frequent use of gamma spectrometric, magnetometric, and gravimetric surveys in the early stages of prospection, this work provides results that can be useful in exploration.…”
Section: Introductionmentioning
confidence: 99%